High-strength explosion-proof tempered glass as well as preparation process and application thereof

By controlling the component ratio during the preparation of tempered glass and using gamma rays and ultrasonic treatment, the problem of high self-explosion rate of tempered glass is solved, and the preparation of high-strength explosion-proof glass is realized, which is suitable for construction applications.

CN119683839APending Publication Date: 2025-03-25太仓云瑞特种玻璃有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411911120.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

During the preparation process, the self-destruction rate of existing tempered glass is high due to the phase change of nickel sulfide, which affects its application in construction.

Method used

By controlling the mass percentage of each component in the glass liquid, and using gamma ray irradiation and ultrasonic treatment during physical and chemical tempering, the phase change of nickel sulfide is promoted, thereby reducing the self-destruction rate.

Benefits of technology

The prepared high-strength explosion-proof tempered glass has good impact strength, bending strength and surface compressive stress, and the self-destruction rate is significantly reduced, which is suitable for a variety of applications in construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683839A_ABST
    Figure CN119683839A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of tempered glass manufacturing, and particularly relates to high-strength explosion-proof tempered glass as well as a preparation process and application thereof. The preparation process of the high-strength explosion-proof tempered glass mainly comprises the following steps: S1, weighing the components according to the mass percent, grinding and uniformly mixing to obtain glass raw powder; s2, melting the glass raw powder into a standby glass liquid, preparing a primary glass plate, and then cutting, edging and cleaning the glass plate according to use requirements to obtain formed glass; s3, carrying out physical tempering on the formed glass; and S4, performing chemical tempering on the molded glass subjected to physical tempering to obtain the high-strength explosion-proof tempered glass. According to the high-strength explosion-proof tempered glass as well as the preparation process and the application thereof, the prepared tempered glass for buildings has relatively good impact strength, bending strength and surface compressive stress, and also has relatively low spontaneous explosion rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tempered glass manufacturing, and specifically relates to high-strength explosion-proof tempered glass and a preparation process and application thereof. Background Art

[0002] Tempered glass is a kind of glass with compressive stress on the surface. In order to improve the strength of glass, chemical or physical methods are usually used to form compressive stress on the glass surface. When the glass is subjected to external force, the surface stress is first offset, thereby improving the bearing capacity and enhancing the glass's own wind pressure resistance and impact resistance. With the rapid development of China's economy, the demand for tempered glass in all walks of life has increased dramatically. In the construction industry, tempered glass has also shown many uses. For example, it can be used as anti-vibration and anti-collision parts such as door and window glass, partitions and public places, so there are extremely high requirements for the various properties of tempered glass.

[0003] At the same time, compared with ordinary glass, tempered glass also has the defect of self-explosion. There are many reasons for the self-explosion of tempered glass, among which the phase change of nickel sulfide crystals is the main cause of the self-explosion of tempered glass. Nickel sulfide is a crystal with two crystal phases, high-temperature phase α-NiS and low-temperature phase β-NiS. The phase change temperature is 379°C. In the process of preparing tempered glass, the heating temperature is much higher than the phase change temperature of nickel sulfide, so that all nickel sulfide is converted into high-temperature phase α-NiS. In the subsequent rapid cooling process, the high-temperature phase α-NiS has no time to convert into low-temperature phase β-NiS and is frozen in the tempered glass. At room temperature, the high-temperature phase α-NiS is in an unstable state and has a tendency to gradually transform into low-temperature phase β-NiS. This transformation is accompanied by a volume expansion of 2% to 4%, which makes the tempered glass bear huge phase change tensile stress, thereby causing the tempered glass to self-explode. Therefore, the performance of tempered glass used in buildings needs to be further improved, and the self-explosion rate also needs to be further reduced. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a high-strength explosion-proof tempered glass and a preparation process and application thereof, with the purpose of preparing a high-strength explosion-proof tempered glass for construction, so that the prepared tempered glass for construction has good impact strength, bending strength and surface compressive stress, and at the same time has a low self-explosion rate.

[0005] In order to achieve the above object, the present invention provides a preparation process of high-strength explosion-proof tempered glass, comprising the following steps:

[0006] Step S1, weigh SiO according to mass percentage 2 , B 2 O 3 , Al 2 O 3 , CaO, Na 2O, K 2 O, MgO, Fe 2 O 3 , ZrO 2 , PbO, Bi 2 O 3 and ZnO, grinding the above components in a ball mill and mixing them evenly to obtain glass raw powder;

[0007] Step S2, placing raw glass powder in a crucible, and placing the crucible in a lifting furnace, heating it to 1740-1780° C., keeping it warm for 6 hours, then cooling it to 1600-1640° C., and keeping it warm for another 2 hours to melt it into a glass liquid to be used, injecting the glass liquid to be used into a molding machine, pressing it to obtain a preliminary glass plate, and then naturally cooling it to room temperature in the air, and then cutting, grinding and cleaning the glass plate according to the use needs to obtain a molded glass;

[0008] Step S3, physically tempering the molded glass, placing the molded glass in a mold, and then placing the molded glass in a tempering furnace, gradually heating it to 680-720° C., keeping it warm for 10-15 minutes, and then quickly placing the molded glass in an air grid for rapid cooling, and blowing high-pressure cold air to both sides of the glass with a nozzle to quickly and evenly cool the glass to room temperature, irradiating the glass with gamma rays during the cooling process, and treating the glass with ultrasound;

[0009] Step S4, chemical tempering, places the physically tempered shaped glass in molten salt for ion exchange treatment, cools the glass after completion, and irradiates the glass with gamma rays during the cooling process to obtain high-strength explosion-proof tempered glass.

[0010] Furthermore, in step S1, the mass percentages of the substances in the glass liquid are: SiO 2 50~60%, B 2 O 3 3~4%,Al 2 O 3 4-7%, CaO 5-7%, Na 2 O is 9-13%, K 2 O is 7-9%, MgO is 5-8%, Fe 2 O 3 0.01~0.05%, ZrO 2 4-7%, PbO 1-3%, Bi 2 O 3 It is 1~4%, and ZnO is 1~3%.

[0011] Furthermore, in step S3, the gradient temperature increase is to increase the temperature to 510°C at a rate of 15°C / min, keep it warm for 2 to 4 minutes, then increase the temperature to 600°C at a rate of 10°C / min, keep it warm for 5 to 8 minutes, and then increase the temperature to 680 to 720°C at a rate of 5°C / min.

[0012] Further, in step S3, the radiation dose rate of the gamma ray is 3.6-15.6 kGy / h.

[0013] Furthermore, in step S3, the frequency of the ultrasonic wave is 20-24 Hz.

[0014] Furthermore, in step S4, the temperature of the molten salt is 420-450° C.; the time of the ion exchange treatment is 4-6 hours; and the radiation dose rate of the gamma ray is 3.6-15.6 kGy / h.

[0015] Furthermore, the molten salt is one or more of nitrate molten salt, hydrochloride molten salt, carbonate molten salt and nitrite molten salt.

[0016] Furthermore, the cations in the molten salt include lithium ions (Li + ), sodium ion (Na + ), potassium ion (K + ), rubidium ions (Rb + ), cesium ion (Cs + ) and francium ions (Fr + )

[0017] The present invention also provides a high-strength explosion-proof tempered glass, which is prepared by using the above-mentioned preparation process of the high-strength explosion-proof tempered glass.

[0018] The present invention also provides an application of high-strength explosion-proof tempered glass in buildings, wherein the high-strength explosion-proof tempered glass is used for one or more of exterior walls, curtain walls, skylights, balconies, interior partitions, cabinet doors, glass floors, stair baffles and entrances and exits of public buildings.

[0019] Beneficial Effects

[0020] The invention discloses a preparation process of high-strength explosion-proof tempered glass. By controlling the content of each component and adjusting the process of physical tempering and chemical tempering, the prepared architectural tempered glass has good impact strength, bending strength and surface compressive stress. Meanwhile, when preparing the architectural high-strength explosion-proof tempered glass, gamma rays are used to irradiate the glass and ultrasonic waves are used to treat the glass during the cooling process, so that nickel sulfide in the glass can be promoted to be transformed from a high-temperature phase α-NiS to a low-temperature phase β-NiS, thereby reducing the self-explosion of the prepared architectural high-strength explosion-proof tempered glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention is a flow chart of a preparation process of high-strength explosion-proof tempered glass. DETAILED DESCRIPTION

[0022] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.

[0023] Example 1

[0024] A preparation process of high-strength explosion-proof tempered glass for construction, comprising the following steps:

[0025] Step S1: Based on 1000g of raw glass powder, weigh 520g of SiO 2 , 32gB 2 O 3 ,54gAl 2 O 3 , 55gCaO, 100gNa 2 O,72gK 2 O, 67gMgO, 0.2gFe 2 O 3 ,54gZrO 2 , 10gPbO, 15gBi 2 O 3 , 20.8g ZnO, grind the above components in a ball mill, mix them evenly, and obtain glass raw powder;

[0026] Step S2, placing raw glass powder in a crucible, and placing the crucible in a lifting furnace, heating it to 1740°C, keeping it for 6 hours, then cooling it to 1620°C, and keeping it for another 2 hours to melt it into a glass liquid to be used, injecting the glass liquid to be used into a molding machine, pressing it to obtain a preliminary glass plate, and then naturally cooling it to room temperature in the air, and then cutting, grinding and cleaning the glass plate according to the use needs to obtain a molded glass;

[0027] Step S3, physically tempering the molded glass, placing the molded glass in a mold, and then placing the molded glass in a tempering furnace, heating it to 510°C at a rate of 15°C / min, keeping it warm for 3 minutes, then heating it to 600°C at a rate of 10°C / min, keeping it warm for 6 minutes, and then heating it to 690°C at a rate of 5°C / min, keeping it warm for 13 minutes, and then quickly placing the molded glass on a wind grid for rapid cooling, and blowing high-pressure cold air to both sides of the glass with a nozzle to quickly and evenly cool the glass to room temperature. During the cooling process, the glass is irradiated with gamma rays, and the radiation dose rate is 6.8 kGy / h. At the same time, the glass is treated with ultrasound, and the frequency of the ultrasound is 21 Hz;

[0028] Step S4, chemical tempering, placing the physically tempered shaped glass in a potassium nitrate molten salt at 420°C for 5 hours of ion exchange treatment, cooling the glass after completion, and irradiating the glass with gamma rays during the cooling process, with a radiation dose rate of 6.8 kGy / h, to obtain high-strength explosion-proof tempered glass for construction.

[0029] Example 2

[0030] A preparation process of high-strength explosion-proof tempered glass for construction, comprising the following steps:

[0031] Step S1: Based on 1000g of raw glass powder, weigh 550g of SiO 2 , 38gB 2 O 3 , 40gAl 2 O 3 , 52gCaO, 90gNa 2 O,75gK 2 O, 64gMgO, 0.3gFe 2 O 3 ,52gZrO 2 , 14.7gPbO, 12gBi 2 O 3 , 12g ZnO, grind the above components in a ball mill, mix them evenly, and obtain glass raw powder;

[0032] Step S2, placing raw glass powder in a crucible, and placing the crucible in a lifting furnace, heating it to 1760°C, keeping it for 6 hours, then cooling it to 1620°C, and keeping it for another 2 hours to melt it into a glass liquid to be used, injecting the glass liquid to be used into a molding machine, pressing it to obtain a preliminary glass plate, and then naturally cooling it to room temperature in the air, and then cutting, grinding and cleaning the glass plate according to the use needs to obtain a molded glass;

[0033] Step S3, physically tempering the molded glass, placing the molded glass in a mold, and then placing the molded glass in a tempering furnace, heating it to 510°C at a rate of 15°C / min, keeping it warm for 3 minutes, then heating it to 600°C at a rate of 10°C / min, keeping it warm for 7 minutes, and then heating it to 700°C at a rate of 5°C / min, keeping it warm for 13 minutes, and then quickly placing the molded glass on a wind grid for rapid cooling, and blowing high-pressure cold air to both sides of the glass with a nozzle to quickly and evenly cool the glass to room temperature. During the cooling process, the glass is irradiated with gamma rays, and the radiation dose rate is 10.4 kGy / h. At the same time, the glass is treated with ultrasound, and the frequency of the ultrasound is 22 Hz;

[0034] Step S4, chemical tempering, placing the physically tempered shaped glass in a potassium nitrate molten salt at 440°C for 5 hours of ion exchange treatment, cooling the glass after completion, and irradiating the glass with gamma rays during the cooling process, with a radiation dose rate of 10.4 kGy / h, to obtain high-strength explosion-proof tempered glass for construction.

[0035] Example 3

[0036] A preparation process of high-strength explosion-proof tempered glass for construction, comprising the following steps:

[0037] Step S1: Based on 1000g of raw glass powder, weigh 580g of SiO 2 ,31gB 2 O 3 ,43gAl 2 O 3 , 52gCaO, 90gNa 2 O,74gK 2 O, 50gMgO, 0.2gFe 2 O 3 ,42gZrO 2 , 14gPbO, 12.8gBi 2 O 3 , 11g ZnO, grind the above components in a ball mill, mix them evenly, and obtain glass raw powder;

[0038] Step S2, placing raw glass powder in a crucible, and placing the crucible in a lifting furnace, heating it to 1780°C, keeping it for 6 hours, then cooling it to 1630°C, and keeping it for another 2 hours to melt it into a glass liquid to be used, injecting the glass liquid to be used into a molding machine, pressing it to obtain a preliminary glass plate, and then naturally cooling it to room temperature in the air, and then cutting, grinding and cleaning the glass plate according to the use needs to obtain a molded glass;

[0039] Step S3, physically tempering the molded glass, placing the molded glass in a mold, and then placing the molded glass in a tempering furnace, heating it to 510°C at a rate of 15°C / min, keeping it warm for 4 minutes, then heating it to 600°C at a rate of 10°C / min, keeping it warm for 7 minutes, and then heating it to 720°C at a rate of 5°C / min, keeping it warm for 14 minutes, and then quickly placing the molded glass on a wind grid for rapid cooling, and blowing high-pressure cold air to both sides of the glass with a nozzle to quickly and evenly cool the glass to room temperature. During the cooling process, the glass is irradiated with gamma rays, and the radiation dose rate is 14.8 kGy / h. At the same time, the glass is treated with ultrasound, and the frequency of the ultrasound is 24 Hz;

[0040] Step S4, chemical tempering, placing the physically tempered shaped glass in a molten salt of potassium nitrate and rubidium nitrate (1:1) at 450°C for 6 hours of ion exchange treatment, cooling the glass after completion, and irradiating the glass with gamma rays during the cooling process, with a radiation dose rate of 14.8 kGy / h, to obtain high-strength explosion-proof tempered glass for construction.

[0041] Comparative Example 1

[0042] A process for preparing glass comprises the following steps:

[0043] Step S1: Based on 1000g of raw glass powder, weigh 520g of SiO 2 , 32gB 2 O 3 ,54gAl 2 O 3 , 55gCaO, 100gNa 2 O,72gK 2 O, 67gMgO, 0.2gFe 2 O 3 ,54gZrO 2 , 10gPbO, 15gBi 2 O 3 , 20.8g ZnO, grind the above components in a ball mill, mix them evenly, and obtain glass raw powder;

[0044] Step S2, placing the raw glass powder in a crucible, and placing the crucible in a lifting furnace, heating it to 1740°C, keeping it warm for 6 hours, then cooling it to 1620°C, and keeping it warm for another 2 hours to melt it into a glass liquid to be used, injecting the glass liquid to be used into a molding machine, pressing it to obtain a preliminary glass plate, and then naturally cooling it to room temperature in the air, and then cutting, grinding and cleaning the glass plate according to the needs of use to obtain a formed glass.

[0045] Comparative Example 2

[0046] A process for preparing tempered glass for construction comprises the following steps:

[0047] Step S1: Based on 1000g of raw glass powder, weigh 520g of SiO 2 , 32gB 2 O 3 ,54gAl 2 O 3 , 55gCaO, 100gNa 2 O,72gK 2 O, 67gMgO, 0.2gFe 2 O 3 ,54gZrO 2 , 10gPbO, 15gBi2 O 3 , 20.8g ZnO, grind the above components in a ball mill, mix them evenly, and obtain glass raw powder;

[0048] Step S2, placing raw glass powder in a crucible, and placing the crucible in a lifting furnace, heating it to 1740°C, keeping it for 6 hours, then cooling it to 1620°C, and keeping it for another 2 hours to melt it into a glass liquid to be used, injecting the glass liquid to be used into a molding machine, pressing it to obtain a preliminary glass plate, and then naturally cooling it to room temperature in the air, and then cutting, grinding and cleaning the glass plate according to the use needs to obtain a molded glass;

[0049] Step S3, physically tempering the molded glass, placing the molded glass in a mold, and then placing the molded glass in a tempering furnace, heating it to 510°C at a rate of 15°C / min, keeping it warm for 3 minutes, then heating it to 600°C at a rate of 10°C / min, keeping it warm for 6 minutes, and then heating it to 690°C at a rate of 5°C / min, keeping it warm for 13 minutes, and then quickly placing the molded glass on a wind grid for rapid cooling, and blowing high-pressure cold air to both sides of the glass with a nozzle to quickly and evenly cool the glass to room temperature. During the cooling process, the glass is irradiated with gamma rays, and the radiation dose rate is 6.8kGy / h. At the same time, the glass is treated with ultrasound, and the frequency of the ultrasound is 21Hz to obtain tempered glass for construction.

[0050] Comparative Example 3

[0051] A process for preparing tempered glass for construction comprises the following steps:

[0052] Step S1: Based on 1000g of raw glass powder, weigh 520g of SiO 2 , 32gB 2 O 3 ,54gAl 2 O 3 , 55gCaO, 100gNa 2 O,72gK 2 O, 67gMgO, 0.2gFe 2 O 3 ,54gZrO 2 , 10gPbO, 15gBi 2 O 3 , 20.8g ZnO, grind the above components in a ball mill, mix them evenly, and obtain glass raw powder;

[0053] Step S2, placing raw glass powder in a crucible, and placing the crucible in a lifting furnace, heating it to 1740°C, keeping it for 6 hours, then cooling it to 1620°C, and keeping it for another 2 hours to melt it into a glass liquid to be used, injecting the glass liquid to be used into a molding machine, pressing it to obtain a preliminary glass plate, and then naturally cooling it to room temperature in the air, and then cutting, grinding and cleaning the glass plate according to the use needs to obtain a molded glass;

[0054] Step S3, chemically tempering the molded glass, placing the molded glass in potassium nitrate molten salt at 420°C for 5 hours of ion exchange treatment, cooling the glass after completion, and irradiating the glass with gamma rays during the cooling process, with a radiation dose rate of 6.8 kGy / h, to obtain tempered glass for construction.

[0055] Comparative Example 4

[0056] A process for preparing tempered glass for construction comprises the following steps:

[0057] Step S1: Based on 1000g of raw glass powder, weigh 520g of SiO 2 , 32gB 2 O 3 ,54gAl 2 O 3 , 55gCaO, 100gNa 2 O,72gK 2 O, 67gMgO, 0.2gFe 2 O 3 ,54gZrO 2 , 10gPbO, 15gBi 2 O 3 , 20.8g ZnO, grind the above components in a ball mill, mix them evenly, and obtain glass raw powder;

[0058] Step S2, placing raw glass powder in a crucible, and placing the crucible in a lifting furnace, heating it to 1740°C, keeping it for 6 hours, then cooling it to 1620°C, and keeping it for another 2 hours to melt it into a glass liquid to be used, injecting the glass liquid to be used into a molding machine, pressing it to obtain a preliminary glass plate, and then naturally cooling it to room temperature in the air, and then cutting, grinding and cleaning the glass plate according to the use needs to obtain a molded glass;

[0059] Step S3, physically tempering the molded glass, placing the molded glass in a mold, and then placing the molded glass in a tempering furnace, heating it to 510°C at a rate of 15°C / min, keeping it warm for 3 minutes, then heating it to 600°C at a rate of 10°C / min, keeping it warm for 6 minutes, then heating it to 690°C at a rate of 5°C / min, keeping it warm for 13 minutes, and then quickly placing the molded glass on a wind grid for rapid cooling, and the nozzle blows high-pressure cold air to both sides of the glass, so that the glass is quickly and evenly cooled to room temperature;

[0060] Step S4, chemical tempering, placing the physically tempered shaped glass in potassium nitrate molten salt at 420° C. for 5 hours of ion exchange treatment, and then cooling the glass to obtain tempered glass for construction.

[0061] Analysis of glass performance data obtained in the embodiments and comparative examples

[0062] The mass percentages of the components in Examples 1 to 3 and Comparative Examples 1 to 4 are summarized in Table 1, and the performance data of the prepared glasses are summarized in Table 2. In Examples 1 to 3, when preparing high-strength explosion-proof tempered glass for construction, the molded glass was physically and chemically tempered, while the molded glass was not physically and chemically tempered in Comparative Example 1, the molded glass was only physically tempered in Comparative Example 2, and the molded glass was only chemically tempered in Comparative Example 3. Compared with Comparative Examples 1 to 3, the high-strength explosion-proof tempered glass for construction prepared in Examples 1 to 3 all have good impact strength, bending strength and surface compressive stress.

[0063] At the same time, when preparing high-strength explosion-proof tempered glass for construction in Examples 1 to 3, gamma rays are used to irradiate the glass and ultrasonic waves are used to treat the glass during the cooling process of the glass, which can promote the transformation of nickel sulfide in the glass from high-temperature phase α-NiS to low-temperature phase β-NiS, and can reduce the self-explosion of the prepared high-strength explosion-proof tempered glass for construction, while Comparative Example 4 does not use gamma rays to irradiate the glass and ultrasonic waves to treat the glass. Compared with Comparative Example 4, the high-strength explosion-proof tempered glass for construction prepared in Examples 1 to 3 all have a lower self-explosion rate.

[0064] Table 1 Mass percentage of each component in the examples and comparative examples

[0065]

[0066]

[0067] Table 2 Performance data of glass obtained in the examples and comparative examples

[0068]

Claims

1. A preparation process of high-strength explosion-proof tempered glass, characterized in that: The steps include: Step S1, weighing SiO2, B2O3, Al2O3, CaO, Na2O, K2O, MgO, Fe2O3, ZrO2, PbO, Bi2O3 and ZnO according to mass percentage, grinding the above components in a ball mill, mixing them evenly, and obtaining raw glass powder; Step S2, placing raw glass powder in a crucible, and placing the crucible in a lifting furnace, heating it to 1740-1780°C, keeping it at that temperature for 6 hours, then cooling it to 1600-1640°C, and keeping it at that temperature for another 2 hours, melting it into a glass liquid to be used, injecting the glass liquid to be used into a molding machine, pressing it to obtain a preliminary glass plate, and then naturally cooling it to room temperature in the air, and then cutting, grinding and cleaning the glass plate according to the use needs to obtain a molded glass; Step S3, physically tempering the molded glass, placing the molded glass in a mold, and then placing the molded glass in a tempering furnace, gradually heating it to 680-720°C, keeping it warm for 10-15 minutes, and then quickly placing the molded glass in an air grid for rapid cooling, and blowing high-pressure cold air to both sides of the glass with a nozzle to quickly and evenly cool the glass to room temperature, irradiating the glass with gamma rays during the cooling process, and treating the glass with ultrasound; Step S4, chemical tempering, places the physically tempered shaped glass in molten salt for ion exchange treatment, cools the glass after completion, and irradiates the glass with gamma rays during the cooling process to obtain high-strength explosion-proof tempered glass.

2. The preparation process of a high-strength explosion-proof tempered glass according to claim 1 is characterized in that: In step S1, the mass percentage of each substance in the glass liquid is: SiO2 is 50-60%, B2O3 is 3-4%, Al2O3 is 4-7%, CaO is 5-7%, Na2O is 9-13%, K2O is 7-9%, MgO is 5-8%, Fe2O3 is 0.01-0.05%, ZrO2 is 4-7%, PbO is 1-3%, Bi2O3 is 1-4%, and ZnO is 1-3%.

3. The preparation process of a high-strength explosion-proof tempered glass according to claim 1 is characterized in that: In step S3, the gradient temperature increase is to increase the temperature to 510°C at a rate of 15°C / min, keep it warm for 2-4 minutes, then increase the temperature to 600°C at a rate of 10°C / min, keep it warm for 5-8 minutes, and then increase the temperature to 680-720°C at a rate of 5°C / min.

4. The preparation process of a high-strength explosion-proof tempered glass according to claim 1 is characterized in that: In step S3, the gamma ray radiation dose rate is 3.6-15.6 kGy / h.

5. The preparation process of a high-strength explosion-proof tempered glass according to claim 1 is characterized in that: In step S3, the frequency of the ultrasonic wave is 20-24 Hz.

6. The preparation process of the high-strength explosion-proof tempered glass according to claim 1 is characterized in that: In step S4, the temperature of the molten salt is 420-450° C.; the time of the ion exchange treatment is 4-6 hours; and the radiation dose rate of the gamma ray is 3.6-15.6 kGy / h.

7. The preparation process of the high-strength explosion-proof tempered glass according to claim 6 is characterized in that: The molten salt is one or more of nitrate molten salt, hydrochloride molten salt, carbonate molten salt and nitrite molten salt.

8. The preparation process of the high-strength explosion-proof tempered glass according to claim 7 is characterized in that: The cations in the molten salt include lithium ions (Li + ), sodium ion (Na + ), potassium ion (K + ), rubidium ions (Rb + ), cesium ion (Cs + ) and francium ions (Fr + ) 9. A high-strength explosion-proof tempered glass, characterized in that: The glass is prepared by the preparation process of the high-strength explosion-proof tempered glass according to any one of claims 1 to 8.

10. Application of high-strength explosion-proof tempered glass in buildings, characterized in that: The high-strength explosion-proof tempered glass described in claim 9 is used for one or more of exterior walls, curtain walls, skylights, balconies, interior partitions, cabinet doors, glass floors, stair baffles and entrances and exits of public buildings.